Non-Pharmacological Education on the Use of Cucumber Juice among Elderly Individuals with Hypertension in Perbarakan Village - Fiyola Ladyvia; Ismah Khaerunisa; Rosmawaty Irma Suryani Siagian; Yatini Yatini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Hypertension is a major health problem among the elderly, with an increasing prevalence and a high risk of cardiovascular complications, including coronary heart disease, heart failure, and stroke. This condition requires sustainable and comprehensive management. In addition to pharmacological therapy, non-pharmacological approaches are essential in hypertension control, particularly through health education and the use of easily accessible natural resources. Cucumber (Cucumis sativus) is a potential natural ingredient that may support blood pressure control due to its potassium content, high water composition, and antioxidant properties that contribute to electrolyte balance and blood pressure regulation. This community service activity aimed to improve elderly individuals’ knowledge and understanding of hypertension and the benefits of cucumber juice as a supportive non-pharmacological strategy for blood pressure control. The program was implemented through health education sessions, interactive discussions, and practical demonstrations of simple and applicable cucumber juice preparation. The participants were elderly individuals with hypertension living in the community. Evaluation was conducted by assessing participants’ engagement, comprehension of the material, and changes in attitudes before and after the educational intervention. The results demonstrated the success of the program, as evidenced by an increase in participants with good knowledge from 0% before the intervention to 91.1% after the intervention. In addition, 88.9% of participants expressed willingness to regularly consume cucumber juice as part of their daily hypertension management. In conclusion, non-pharmacological education on the utilization of cucumber juice is effective as a promotive and preventive approach to support blood pressure control among the elderly in the community.